1962
DOI: 10.1149/1.2425424
|View full text |Cite
|
Sign up to set email alerts
|

Nickel-Cadmium Cells

Abstract: its poor electrode efficiency is attributed to the fact that dialuric acid undergoes air oxidation readily. The high electrode efficiencies of hydroquinone and quinhydrone (in excess of 100%) have been shown to be due to a continued oxidation of the products of the initial oxidation reaction, i.e., p-quinone itself is easily oxidized in alkaline electrolyte (2).The electrochemical behavior of the alloxan-dialuric acid system, which has previously been studied polarographically (8), further emphasizes the aroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

1964
1964
2003
2003

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 2 publications
2
13
0
Order By: Relevance
“…Both Salkind (11) and Falk (3) consider the x-ray diffraction patterns in which some Ni(OH)2 lines disappear and others appear as implying a solid solution phase transformation between Ni(OH)2 and beta phase. On the other hand, Foerster (9) in 1907 considered the oxidation to proceed with the formation of a new phase, a solid solution of tetravalent nickel in a trivalent oxide.…”
Section: Nickel Electrodesmentioning
confidence: 99%
“…Both Salkind (11) and Falk (3) consider the x-ray diffraction patterns in which some Ni(OH)2 lines disappear and others appear as implying a solid solution phase transformation between Ni(OH)2 and beta phase. On the other hand, Foerster (9) in 1907 considered the oxidation to proceed with the formation of a new phase, a solid solution of tetravalent nickel in a trivalent oxide.…”
Section: Nickel Electrodesmentioning
confidence: 99%
“…However, the two processes most p r o b a b l y responsible for these features, and their redox potentials, E1 and E2, interpolated or calculated from the literature (31, 32) for (i) 15M NaOH at room temuerature (calculated pH 17) and (ii) 30% KOH at 70~ (calculated pH 14.9), respectively, are trodes (34,35), of the conversion of Ni(OH)9. to ~-NiOOH at this potential cannot be lightly dismissed. However, the two processes most p r o b a b l y responsible for these features, and their redox potentials, E1 and E2, interpolated or calculated from the literature (31, 32) for (i) 15M NaOH at room temuerature (calculated pH 17) and (ii) 30% KOH at 70~ (calculated pH 14.9), respectively, are trodes (34,35), of the conversion of Ni(OH)9. to ~-NiOOH at this potential cannot be lightly dismissed.…”
Section: Methodsmentioning
confidence: 99%
“…Some cufi-uaiin in investigations of the silver electrode has beo, cau sed by the report of Jones and Thirsk (6) of what they believed was the x -ray diffracti-n patern of AgO. The pattern reported has since been shown to be that of the so-called silver peroxysulfate Ag 7 OSO 4 and not AgO (7). Bi iggs, Dugdale, and Wynne-Jones (2) confirmed that the final product of anodizing Ag in H 2 SO 4 was mainly the peroxysulfate and not AgO.…”
Section: Application Of This Cell To the Silver Electrode In Koh Solumentioning
confidence: 99%